2015 IEEE MTT-S International Microwave Symposium 2015
DOI: 10.1109/mwsym.2015.7167005
|View full text |Cite
|
Sign up to set email alerts
|

11 THz figure-of-merit phase-change RF switches for reconfigurable wireless front-ends

Abstract: We report on GeTe-based, phase-change RF switches in a series configuration with an embedded micro heater for thermal switching. With heater parasitics reduced, these GeTe RF switches show on-state resistance of 0.12 ohm*mm and off-state capacitance of 0.12 pF/mm. The RF switch figure-of-merit is estimated to be 11 THz, which is about 15 times better than state-of-the-art silicon-on insulator switches. With 50-J.lm-wide GeTe switches, RF insertion loss was 0.25 dB and isolation was 24 dB at 20 GHz.Harmonic pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
(6 reference statements)
2
18
0
Order By: Relevance
“…Linearity is one of the important parameters to evaluate phase and frequency distortions. It is reported that GeTe based switches show good linear characteristics which is evident from its reported third order power intercept values (varies~27 dBm to 55 dBm) [24][25][26][27][28][29][30][31][32][33]. Ha reported that at high bias current, VO 2 also shows very good linear response till 27 dBm power [49].…”
Section: Performance Benchmarking Of Gete and Vomentioning
confidence: 90%
See 2 more Smart Citations
“…Linearity is one of the important parameters to evaluate phase and frequency distortions. It is reported that GeTe based switches show good linear characteristics which is evident from its reported third order power intercept values (varies~27 dBm to 55 dBm) [24][25][26][27][28][29][30][31][32][33]. Ha reported that at high bias current, VO 2 also shows very good linear response till 27 dBm power [49].…”
Section: Performance Benchmarking Of Gete and Vomentioning
confidence: 90%
“…They reported that their switches able to demonstrate ON resistance approximately 0.3 Ω, insertion loss <0.1 dB at 40 GHz, isolation approximately 30 dB at 40 GHz, third order intercept point >50 dBm, power handling capability approximately 3-10 W, and contrast in resistance approximately 10 5 . Later in Reference [32], the authors fabricated a RF switch with an embedded refractory microheater in series configuration. In this work, they characterize the switching structure with two different widths; 50 µm and 150 µm.…”
Section: Device Fabrication and Rf Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracted resistance when the state is On, R ON ≈ 11 ohms and capacitance when the state is Off, C OFF ≈ 7.7 fF. This results in a cut-off frequency, which is used to estimate the RF switches (a figure of merit (FOM)) [29,30] f co = 1/(2πR ON C OFF ) ≈ 1.8 THz. Further improvements, especially in terms of scaling, are expected to lead to a significant increase in FOM.…”
Section: High-frequency 2d Mos 2 Memristorsmentioning
confidence: 99%
“…Further improvements, especially in terms of scaling, are expected to lead to a significant increase in FOM. A unique combination of independent LRS resistance and area-dependent HRS capacity gives a FOM that can be scaled to 100 s of THz by reducing the area of the device that determines advantages over phase-change switches [29,30], where the capacitance is proportional to the width, but R ON is inversely dependent, hence, prevents frequency scaling without significant compromise losses. In addition, the high stress of mechanical rupture and the easy integration of 2D materials onto soft substrates enable the production of flexible nonvolatile digital and analog/RF switches capable of withstanding mechanical cycling (Figure 22(e)).…”
Section: High-frequency 2d Mos 2 Memristorsmentioning
confidence: 99%